2003
DOI: 10.2460/ajvr.2003.64.1030
|View full text |Cite
|
Sign up to set email alerts
|

Geometric symmetry of the solar surface of hooves of Thoroughbred racehorses

Abstract: When the angle bisected by the collateral sulci is used to determine the dorsopalmar axis of the hoof, most central structures (bars and collateral sulci) have mediolateral symmetry. However, the hoof wall and sole have some mediolateral asymmetries and most structures have dorsopalmar asymmetry. These findings may assist the development of devices for attachment to hooves and studies of the interaction of hooves with bearing surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…The majority of the foot conformation parameters measured in this study showed a significant degree of asymmetry within a hoof, in common with the findings of a number of other studies [3,[18][19][20][21]. This asymmetry suggests that a geometrically balanced foot is rare in the group of horses studied here, even in recently trimmed horses.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the foot conformation parameters measured in this study showed a significant degree of asymmetry within a hoof, in common with the findings of a number of other studies [3,[18][19][20][21]. This asymmetry suggests that a geometrically balanced foot is rare in the group of horses studied here, even in recently trimmed horses.…”
Section: Discussionsupporting
confidence: 89%
“…Because drop test results depend on contact area, mass, and drop height [13], the TTD was developed to simulate the surface area, effective mass, and hoof impact velocity of a Thoroughbred horse at a slow gallop or fast trot. The diameter was determined using reported average width and length measurements of Thoroughbred racehorse hooves [14]. Trot and canter data (horse speed of 5-8 m/s) from an instrumented horse study on dirt, synthetic, and turf surfaces suggest the effective mass at impact is between 20 and 40 kg and average vertical hoof landing velocity is approximately 2-3 m/s [4,15].…”
Section: Methodsmentioning
confidence: 99%
“…The shape of the ground surface of the ground plate was based on previously reported data describing the solar surface of the hoof (Roland et al, 2003).…”
Section: Design Descriptionmentioning
confidence: 99%